Rancang Bangun GPS Back Track Pada Rekaman Rute Pendakian Menggunakan Sistem Embedded - Agung Prasetyo; Dahnial Syauqy; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mountain climbing is one of nature's exploration activities that requires knowledge in understanding the map and area to be passed. However, not all climbers have knowledge of navigation, its causing the risk of getting lost while climbing. Navigation assistant that exist, only guide climbers only first route to final destination and can't save the route that already passed, until it causes climber difficulty going back to first route when they lost. Because that, in minimizing te risk of lost, be required navigation assistant device that cloud show the route has been passed. Based on these problems in this research created a navigation device assistant technology called GPS back track. This device is built with several components such a, the U-Blox Neo 6 M GPS module that functions in retrieving GPS data in the form of latitude and longitude coordinates, LCD display 800 x 480 TFT function displays information in the recording process running routes, Raspberry pi 2B functions process data input and output during the process of recording the route and the main resources for running the entire system using power bank. GPS back track has a feature that is able to open the recorded file that has been created and displayed on the LCD display. Based on the results of GPS accuracy testing, it is known that the GPS module error percentage at latitude coordinates is 3.77505% and longitude is 3.698758%. While in the testing of device recording, tracks and trackbacks functions can record routes and display them on the LCD in the form of route lines that are passed.